2017
DOI: 10.1177/0255761417729544
|View full text |Cite
|
Sign up to set email alerts
|

Talent development in Chinese and Swiss music students

Abstract: Musical talent development and the factors that influence it—such as family or peers—have been widely researched, especially in a Western setting. Despite the growing body of research in non-Western cultures and regions, there is still a lack of research comparing the factors and perceptions of musical talent development between Western and Asian settings. This interview study compared Swiss and Chinese music students’ ( N = 19) musical talent development and the factors influencing musical talent during child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
1
12
0
2
Order By: Relevance
“…Entsprechend erwarteten wir höhere Korrelationen zwischen den Selbstkonzepten in den Schulfächern Musik und Kunst als zwischen dem Selbstkonzept im Schulfach Musik und Selbstkonzepten anderer Schulfächer. Dies lässt sich mit der Ähnlichkeit der Schulfächer Musik und Kunst begründen: Begabung und außerschulisches Engagement spielen in beiden Fächern eine wichtige Rolle für gute Leistungen (Davis 1994;Evans et al 2000;Petersen 2018;vgl. z Verschiedene Studien verweisen darauf, dass sich Jungen und Mädchen nicht in der Struktur verschiedener akademischer Selbstkonzepte unterscheiden (Marsh 1993).…”
Section: Das Selbstkonzept In Musikunclassified
“…Entsprechend erwarteten wir höhere Korrelationen zwischen den Selbstkonzepten in den Schulfächern Musik und Kunst als zwischen dem Selbstkonzept im Schulfach Musik und Selbstkonzepten anderer Schulfächer. Dies lässt sich mit der Ähnlichkeit der Schulfächer Musik und Kunst begründen: Begabung und außerschulisches Engagement spielen in beiden Fächern eine wichtige Rolle für gute Leistungen (Davis 1994;Evans et al 2000;Petersen 2018;vgl. z Verschiedene Studien verweisen darauf, dass sich Jungen und Mädchen nicht in der Struktur verschiedener akademischer Selbstkonzepte unterscheiden (Marsh 1993).…”
Section: Das Selbstkonzept In Musikunclassified
“…Leung and McPherson have identified that in addition to difficulties relating to perceptions of the value of Music which have an impact on uptake of study, there are also issues concerning the curriculum, which they argue needs to move from a functional focus of skills and knowledge assimilation to "authentic experience that involves creating, listening to and performing music" (LEUNG; MCPHERSON, 2010, p.165). These aspects of value and motivation may influence students' and parents' views on the value of Music, and may be connected to perceptions of genre enjoyment and validity: Ho and Law (2006) found preferences for Western classical and popular music among students from Hong Kong, Shanghai and Taipei; however, Petersen (2018) identified that students feel there is less acceptance of jazz and rock than of classical music in China. Ho's analysis of the views of 2971 secondary school students in Beijing revealed that while teachers acknowledged the need for a balanced curriculum including Western and Chinese classical and popular music, they would prefer a "more open and culturally diversified curriculum" containing more popular music and music from other cultures (HO, 2014, p.283).…”
Section: Music Education In China and Hong Kongmentioning
confidence: 99%
“…The tensions of subject content as well as issues of resources and teacher support may have implications for alignment of content and practice when students embark on subsequent programmes of study. While there is a lack of comparative research on learning music at higher education level, Petersen (2018) undertook comparison of a small sample of Chinese and Swiss university music students, finding similarities between their career aims, their views on the role of the teacher, which included the teacher as friend and "role model/mentor" (p.235), and on the relationship between ability levels, effort and talent. Both Swiss and Chinese students expected to find working in the music profession challenging.…”
Section: Internationalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not only cultural, but also societal, familial, or educational circumstances-the social environments (Spychiger, 2017b)-that play a role in shaping the musical self-concept. In this regard, aspects such as socialization, the available music education, or beliefs about inborn potential or practice to achieve musical competence are of importance (Evans et al, 2000;Petersen, 2018). If Chinese students tend to emphasize achievement, this could possibly be explained culturally, since disciplined practice, training, and effort have historically been an important part of the Chinese educational system (e.g., Huang & Gove, 2015).…”
Section: Introductionmentioning
confidence: 99%